Associations of long- and short-term air pollution exposure with markers of inflammation and coagulation in a population sample. Issue 11 (16th August 2009) - Panasevich, S; Leander, K; Rosenlund, M; Ljungman, P; Bellander, T; de Faire, U; Pershagen, G; Nyberg, F
Abstract : Background: Exposure to elevated levels of ambient air pollutants can lead to adverse cardiovascular effects. Potential mechanisms include systemic inflammation and perturbation of the coagulation balance. Objectives: To investigate long- and short-term effects of air pollution exposure on serum levels of inflammatory (IL-6, TNF-α and CRP) and coagulation (fibrinogen and PAI-1) markers relevant for cardiovascular pathology. Methods: The study group consisted of a population sample of 1028 men and 508 women aged 45–70 years from Stockholm. Long-term air pollution exposure was assessed using spatial modelling of traffic-related NO2 and heating-related SO2 emissions at each subject's residential addresses over retrospective periods of 1, 5 and 30 years. Short-term exposure was assessed as averages of rooftop measurements over 12–120 h before blood sampling. Results: Long-term exposures to both traffic-NO2 and heating-SO2 emissions showed consistent associations with IL-6 levels. 30-year average traffic-NO2 exposure was associated with a 64.5% (95% CI 6.7% to 153.8%) increase in serum IL-6 per 28.8 μg/m 3 (corresponding to the difference between the 5th and 95th percentile exposure value), and 30-year exposure to heating-SO2 with a 67.6% (95% CI 7.1% to 162.2%) increase per 39.4 μg/m 3 (5th–95th percentile value difference). The association appeared stronger in non-smokers, physically active people and hypertensive subjects. We observed positive non-significant associations of inflammatory markers with NO2 and PM10 during 24 h before blood sampling. Short-term exposure to O3 was associated with increased, and SO2 with decreased, fibrinogen levels. Conclusions: Our results suggest that exposure to moderate levels of air pollution may influence serum levels of inflammatory markers.